PUSPINDES E-Performance Information System for Monitoring the Performance - Teguh Tamrin; Akhmad Khanif Zyen (Universitas Dian Nuswantoro and IndoCEISS, 2022)
Puspindes is a government institution built by the Pemalang government to provide competence in the field of Information and Communication Technology (ICT) development. The rural informatics empowerment center, hereinafter referred to as PUSPINDES, Pemalang Regency is a flagship program under the supervision and responsibility of BAPERMASDES (Community Empowerment Agency Village) Pemalang Regency this institution focuses on village development, especially in the field of Computer Information Technology and also Intern networks for villages. A system was created to assist in the administrative process carried out by PUSPINDES employees using the PHP Programming Language CodeIgniter package and data storage using a MySQL database.